2016
DOI: 10.22158/rhs.v1n2p85
|View full text |Cite
|
Sign up to set email alerts
|

Towards Promotion of Community rewards to Volunteer Community Health Workers? Lessons from Experiences of Village Health Teams in Luwero, Uganda

Abstract: In the debate regarding volunteer Community Health Workers (CHWs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The remoteness of rural communities has been reported in other studies as a barrier to mothers’ ability to reach the healthcare facilities [ 5 , 39 – 41 ]. These findings suggested the need for effective and sustainable means of transport in community-based interventions designed to improve access by linking communities to the health system through SMAGs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remoteness of rural communities has been reported in other studies as a barrier to mothers’ ability to reach the healthcare facilities [ 5 , 39 – 41 ]. These findings suggested the need for effective and sustainable means of transport in community-based interventions designed to improve access by linking communities to the health system through SMAGs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these have been identified as being significant factors in motivation of CHVs (13, 14, 17, 18, 25, 26). …”
Section: Discussionmentioning
confidence: 99%
“…Whether it is the imparted knowledge, the continuous engagement with the formal health sector, the feeling of belonging, the fringe benefits or a combination of such, it is imperative for programs to continually provide an enabling environment to enhance performance of CHVs. It has been reported by Turinawe et al that although the CHVs in central Uganda were recruited as volunteers they still expected some incentives (26). …”
Section: Discussionmentioning
confidence: 99%
“…Inadequate support and supervision along with weak communication skills in volunteers and instructors were among other problems that the participants mentioned. In an ethnographic study in Uganda, the researchers found that the volunteers needed authorities to clarify how they should communicate with the healthcare team, local government, and medical structures [ 26 ]. Moreover, volunteers in south Africa stated that unsuitable communication with each other and inadequate team supervision were their weak points [ 27 ].…”
Section: Discussionmentioning
confidence: 99%